Mycoplasma detection in a historical arbovirus repository: Commercial kit comparison and implications for improved repository management - Russell, Brandy J.; Horiuchi, Kalanthe; Velez, Jason O.; Goodman, Christin H.; Johnson, Barbara W. (Journal of virological methods, 2020)
•Mycoplasma quality control testing is vital for continued maintenance of historical virus repositories.•Virus preparation (replication host) influences mycoplasma contamination result.•Specific mycoplasma species are maintained within a repository. The Centers for Disease Control and Prevention, Arbovirus Reference Collection (ARC) contains viral isolates from both environmental and human sources that are maintained in the laboratory through passage in suckling mouse brain and/or vertebrate and invertebrate cell culture. There has been increased concern regarding the effect of mycoplasma contamination on virus growth and its impact on research and phenotypic analysis. Therefore, quality control testing of virus preparations has become a routine part of the ARC quality assurance program. We compared the performance of three kits - the PCR Mycoplasma Detection Kit (ABM), the VenorGem Mycoplasma Detection Kit (Sigma), and the MycoAlert Mycoplasma Detection Kit (Lonza) - against a reference mycoplasma detection assay from the American Tissue Culture Collection (ATCC) using 744 virus preparations in the ARC, representing 721 unique viruses comprising twelve families and unclassified viruses. We found the ABM kit had the highest sensitivity and specificity, followed by the Sigma kit and Lonza kit, when compared to the ATCC kit. An increase in false positives was observed for the Lonza kit for preparations recently passaged in suckling mouse. Our data supports previously reported observations; that once introduced a specific species of mycoplasma is maintained within a lab.